Production of novel ceramic materials from coal fly ash and metal finishing wastes - Little, M. R.; Adell, V.; Boccaccini, Aldo R.; Cheeseman, C. R. (Resources Conservation and Recycling, 2008)
Fly ash from coal fired power stations is a potential raw material for the production of ceramic tiles, bricks and blocks. Previous work has demonstrated that the addition of metals can significantly alter fly ash sintering. Metal finishing produces problematic waste filter cakes and sludges that are increasingly difficult to dispose of to landfill. The objective of this research was to investigate the effect of selected metal finishing wastes on the properties of sintered fly ash. A 10 wt.% addition of dried metal finishing sludge obtained from the phosphate bath at a tri-cationic phosphating operation significantly reduced the sintering temperature for maximum density by approximately 75 °C. The addition of the phosphate bath sludge also reduced leaching of As, to the extent that fly ash ceramics containing this waste would be classified as inert. Potential industrial applications for these novel waste-derived ceramic materials are discussed. © 2008 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2008.tech.IW.LM.produc
Keywords: Ceramics; Fly ash; Metal finishing wastes; Pressing; Sintering; Waste reuse